Ciclo de conversión del efectivo y su incidencia en la liquidez de una empresa industrial - Diaz Cuenca, Patrick Ademir (2021)
Objective: To establish the impact of the cash conversion cycle on the liquidity of the industrial company Damar G&L S.A.C of Lima, during 2016 to 2019. Method: The study presented a quantitative approach with a range of cross-sectional correlational, using a non-experimental design. The method used to collect the data was the documentary analysis. As the study population, this research used data from the accounting records of accounts receivable, inventories, and the company’s payable accounts, in which 48 financial monthly statements were structured. Results: The results show that there is a minimal non-significant relationship between the cash conversion cycle and liquidity (Rho = .075, p = .614) corresponding to the periods under study. Furthermore, the independent variable’s indicators, accounts receivable turnover period, inventory turnover period, and accounts payable turnover period, show a weak relationship (Rho = .201, -.267, .086) in the acid test, with a significance level greater than 5%. Conclusion: It is concluded that, during the 2016-2019 period of the company under review, the cash conversion cycle does not directly affect its liquidity.